Comparative Proximate Chemical Composition of Two Invasive Fish Species Siganus rivulatus and Siganus luridus and the Native Species Sciaena umbra off the Western Coast of Tobruk, Eastern Mediterranean Sea - Abtisam Alsaadi; Amani Fitori; Raqi Jabur; Rania Amaizeeg; Ali Miftah; Muhamad Aqeela; Mira Eesa (AlQalam Journal of Medical and Applied Sciences, 2025)
The Mediterranean Sea is increasingly invaded by biological invasions due primarily to the Suez Canal, shipping, and climate change. The present study investigates the proximate chemical composition of two invasive species (Siganus rivulatus and Siganus luridus) and the native Sciaena umbra along the western coast of Tobruk, Libya. Fifteen samples were analyzed for moisture, protein, lipid, ash, and carbohydrate content. The results showed significant interspecific variability, with S. umbra with the highest protein (17.67%) and ash (1.11%) and the lowest carbohydrate (2.72%), which are reflective of its carnivorous/omnivorous feeding. S. rivulatus and S. luridus, on the other hand, had higher carbohydrate (5.14–5.54%) and comparatively higher fat, which are reflective of their herbivorous feeding. Discriminant function analysis (DFA) correctly assigned 93.3% of species as native or invasive. These findings highlight the invasive species’ trophic impacts and provide baseline data for biodiversity conservation and fisheries management in the eastern Mediterranean.